Fluorescence polarization immunoassay of progesterone - Choi, MJ; Choi, J; Yoon, DY; Park, J; Eremin, SA (PHARMACEUTICAL SOC JAPAN, 1997)
A homogeneous fluorescence polarization immunoassay (FPIA) was developed to measure levels of progesterone in urine using a TDx analyzer in photocheck mode (Abbott Labs). Two tracers of ethylenediamine fluorescein thiocarbamyl (EDF) were employed; one was synthesized from 11 alpha-hydroxyhemisuccinate progesterone (Prog-11OH-HS) and the other was synthesized from 3-(o-carboxymethyl)oxime progesterone (Prog-3CMO), Each derivative of progesterone was conjugated with bovine serum albumin and used as an immunogen which produced monoclonal antibody clone 15A (MAb 15A, anti-Prog-11OH-HS) and clone 2B7 (MAb 2B7, anti-Prog-3CMO), respectively, Different combinations of tracers and antibodies were investigated in the FPIA system, Similar sensitivity was observed when using the pair, MAb 2B7 and its homologous tracer, Prog-3CMO-EDF, or MAb 15A and its homologous tracer, Prog-11OH-HS-EDF, In this immunoassay, no separation step was required and the total time for an assay of 10 samples was approximately 7 min, The progesterone detection limit in a 10 mu l sample was 3 ng/ml, The cross-reactivity results indicate that the A-, B- and D-ring of a steroid are buried in the binding pocket of MAb 15A, while the C-ring faced outward, resulting in cross-reactivity with 11-alpha hydroxy progesterone, The A-, B- and C-ring of a steroid of MAb 2B7, in contrast, are buried deep in the pocket leaving the D-ring facing outward, resulting in some different degrees of cross-reactivity with C17 position substituted steroids.
Keywords: MONOCLONAL-ANTIBODIES; SOLID-PHASE; FLUOROIMMUNOASSAY; SPECIFICITY; METHAMPHETAMINE; SERUM